ENT300 Penyangkai Temuai Enterprise / Flora Michelle Anak Tony... [et.al] - Tony, Flora Michelle; Edwin, Jacqueline; Lampong, Willimena; Sayat, Emillia (2017)
The business plan of PENYANGKAI TEMUAI ENTERPRISE is proposed so that it can be undertaken comprehensive manner. This business plan led us toward opportunity to access the business in the future. We decided to make a partnership in this business which we supply factory to produce the fish ball in tire premises, and we also supply it to wet market and supermarket. This business consists of four shareholders. All shareholders had agreed with the amount of contribution, profit and loss will incurred toward each of us. This is to ensure that no one will be discriminated as the profits and losses are divided at the end of the accounting period. Besides, the advantages of having partnership business is that all the shareholders will always share an ideas and knowledge which may led this business to gain more profits and also to achieved high productivity from time to time. In other hand, each partnership also responsible toward their job as each of us have a job which needed to be organized in order to ensure smooth management.